2023
DOI: 10.1002/tox.23996
|View full text |Cite
|
Sign up to set email alerts
|

Selenium reduces acrylamide‐induced testicular toxicity in rats by regulating HSD17B1, StAR, and CYP17A1 expression, oxidative stress, inflammation, apoptosis, autophagy, and DNA damage

Serkan Yildirim,
Emin Sengul,
Emrah Hicazi Aksu
et al.

Abstract: This study investigated the effects of Selenium (Se) on testis toxicity induced by Acrylamide (ACR) in rats. In our study, 50 male adult rats were used, and the rats were divided into five groups; control, ACR, Se0.5 + ACR, Se1 + ACR, and Se1. Se and ACR treatments were applied for 10 days. On the 11th day of the experimental study, intracardiac blood samples from the rats were taken under anesthesia and euthanized. Sperm motility and morphology were evaluated. Dihydrotestosterone, FSH, and LH levels in sera w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…[66] Pro-inflammatory cytokines such as IL-1β cause acute responses of inflammation by inducing the expression of adhesion molecules in endothelial cells, stimulating inflammatory cells, and causing the proliferation of circulating leukocytes. [67] IL-1β generated by macrophages has a paracrine effect on Leydig cells. [68] IL-1β is also plays a role in apoptotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…[66] Pro-inflammatory cytokines such as IL-1β cause acute responses of inflammation by inducing the expression of adhesion molecules in endothelial cells, stimulating inflammatory cells, and causing the proliferation of circulating leukocytes. [67] IL-1β generated by macrophages has a paracrine effect on Leydig cells. [68] IL-1β is also plays a role in apoptotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that selenium deficiency increases the risk of metabolic disorders, such as dyslipidemia, abnormal glucose metabolism, and thyroid hormone dysfunction ( 21 ), through oxidative stress and abnormal activation of the PI3K/Akt signaling pathway ( 22 ). Moreover, Yildirim et al ( 23 ) showed that selenium can prevent oxidative stress-related damage in acrylamide-induced testicular toxicity in rats. In another study, Ibrahim et al ( 24 ) indicated that binaphthyl diselenide could significantly restore the defects of antioxidant defense mechanisms and exert anti-ulcer activity against ethanol-induced gastric injury.…”
Section: Introductionmentioning
confidence: 99%